Using Storybooks to Teach Children About Illness Transmission and Promote Adaptive Health Behavior – A Pilot Study - Conrad, Megan; Kim, Emily; Blacker, Katy-Ann; Walden, Zachary; LoBue, Vanessa (Frontiers in Psychology, 2020)
Although there is a large and growing literature on children’s developing concepts of illness transmission, little is known about how children develop contagion knowledge before formal schooling begins, and how these informal learning experiences can impact children’s health behaviors. Here we asked two important questions: First, do children’s informal learning experiences, such as their experiences reading storybooks, regularly contain causal information about illness transmission; and second, what is the impact of this type of experience on children’s developing knowledge and behavior? In Study 1, we examined whether children’s commercial books about illness regularly contain contagion-relevant causal information. In Study 2, we ran a pilot study examining whether providing children with causal information about illness transmission in a storybook can influence their knowledge and subsequent behavior when presented with a contaminated object. The results from Study 1 suggest that very few (15%) children’s books about illness feature biological causal mechanisms for illness transmission. However, results from Studies 2 suggest that storybooks containing contagion-relevant explanations about illness transmission may encourage learning and avoidance of contaminated objects. Altogether, these results provide preliminary data suggesting that future research should focus on engaging children in learning about contagion and encouraging adaptive health behaviors.